VD_FINDINFO Arrêt / 2020 / 1010 vom 10. November 2020 - VD Tribunal cantonal (2020)
ALLOCATION SOCIALE, AM, PRIME D'ASSURANCE-MALADIE, UNITÉ ÉCONOMIQUE, CONCUBINAGE | 11 al. 1 LVLAMal, 9 al. 1 LVLAMal, 9 al. 2 LVLAMal, 10 al. 1 let. d LHPS, 9 LHPS